The role of taurine in male reproduction: Physiology, pathology and toxicology - Li, Yuanyuan; Peng, Qianwen; Shang, Jia; Dong, Wanglin; Wu, Sijia; Guo, Xiajun; Xie, Zhenxing; Chen, Chaoran (Frontiers in Endocrinology, 2023)
Taurine, a sulfur-containing amino acid, has a wide range of biological effects, such as bile salt formation, osmotic regulation, oxidative stress inhibition, immunomodulation and neuromodulation. Taurine has been proved to be synthesized and abundant in male reproductive organs. Recently, accumulating data showed that taurine has a potential protective effect on reproductive function of male animals. In physiology, taurine can promote the endocrine function of the hypothalamus-pituitary-testis (HPT) axis, testicular tissue development, spermatogenesis and maturation, delay the aging of testicular structure and function, maintain the homeostasis of the testicular environment, and enhance sexual ability. In pathology, taurine supplement may be beneficial to alleviate pathological damage of male reproductive system, including oxidative damage of sperm preservation in vitro, testicular reperfusion injury and diabetes -induced reproductive complications. In addition, taurine acts as a protective agent against toxic damage to the male reproductive system by exogenous substances (e.g. therapeutic drugs, environmental pollutants, radiation). Related mechanisms include reduced oxidative stress, increased antioxidant capacity, inhibited inflammation and apoptosis, restored the secretory activity of the HPT axis, reduced chromosomal variation, enhanced sperm mitochondrial energy metabolism, cell membrane stabilization effect, etc. Therefore, this article reviewed the protective effect of taurine on male reproductive function and its detailed mechanism, in order to provide reference for further research and clinical application.